PENGARUH DESENTRALISASI FISKAL TERHADAP ANGKA MELEK HURUF, DAN ANGKA PARTISIPASI SEKOLAH DI KABUPATEN/KOTA PROVINSI JAWA TENGAH PERIODE 2010 DAN 2011 - Mujiyati Mujiyati; Heppy Purbasari (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta, 2014)
The purpose of Indonesian fiscal decentralization that started on 2001 is focus on the local government development. Fiscal decentralization is believed to createpublic servicesefficiency on local government. Furthermore, fiscal decentralization ensure the local budget (APBD) is spent to develop health and education sectors as these sectors are part of basic needs. This study aims to examine how fiscal decentralization influence to the local educational development in term of literacy rate (AMH) and school enrolment rate (APS). This study uses data based on the kabupaten/kota over Central Java Province in the periods of 2010 – 2011. This study also uses linear regression with non-probability sampling as there is 35 kabupaten/kota each year uses for population and sample in this study. Result shows that fiscal decentralization has an influence to AMH and APS based on the data from kabupaten/kota in Central Javain the periods of 2010 -2011. Thus, it could be conclude that local governments (kabupaten/kota) in Central Java Province have used local revenue to provide public education services specifically in improving literacy and school enrolment rate for 7-15th year students.